Spremembe rabe tal na območjih, ki so strateškega pomena za kmetijstvo in pridelavo hrane v obdobju 2000-2017 - Žiberna, Igor (Revija za geografijo, 2018)
The article analyses land use changes in areas of strategic importance for agriculture and food production in the period 2000-2017 and which, as such, require special treatment in the event of possible changes of cultivated land in non-agriculture land. Land use data published by the Ministry of Agriculture, Forestry and Food is used. Changes in land use are presented at the level of the entire country and at the level of statistical regions. The degree of utilization of these areas for agriculture is shown in particular. The direction of land use changes during the period considered is also analyzed.
Keywords: cultivated land; ekstenzifikacija; extensification; land use changes; obdelovalne površine; raba tal; Slovenia; Slovenija